2021
DOI: 10.1016/j.psj.2020.12.033
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the fiber source and xylanase supplementation on production, egg quality, digestibility, and intestinal morphology in the aged laying hen

Abstract: This study was conducted to evaluate the effects of the fiber source (wheat bran [ WB ] or sugar beet pulp [ SBP ]) and xylanase supplementation on production, egg quality, ileal digestibility, intestinal morphology, and gastrointestinal pH in aged laying hens. A total of 540 laying hens (Lohman LSL Lite; 70 wk of lay) were randomized into 10 treatments (6 replicate cages of 9 birds) consisting of a corn soy control supplemented with 0, 3, or 6% WB or SBP with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Previous studies have reported that the laying performance and egg quality of laying hens gradually decrease at the later stages of laying ( Marzec, et al, 2019 ). Current research on aged laying hens has focused predominantly on issues such as fatty liver, leg problems, and reproductive system diseases, with limited attention devoted to alterations in intestinal function ( Bar et al, 1988 ; Gloux, et al, 2020 ; Zhang, et al, 2020a ; Han, et al, 2020 ; Abdollahi et al, 2021 ; Wang, et al, 2021 ). Intestinal health plays a crucial role in nutritional digestion and absorption, disease resistance, and the overall production performance of aged laying hens ( Saffrey, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the laying performance and egg quality of laying hens gradually decrease at the later stages of laying ( Marzec, et al, 2019 ). Current research on aged laying hens has focused predominantly on issues such as fatty liver, leg problems, and reproductive system diseases, with limited attention devoted to alterations in intestinal function ( Bar et al, 1988 ; Gloux, et al, 2020 ; Zhang, et al, 2020a ; Han, et al, 2020 ; Abdollahi et al, 2021 ; Wang, et al, 2021 ). Intestinal health plays a crucial role in nutritional digestion and absorption, disease resistance, and the overall production performance of aged laying hens ( Saffrey, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A primary challenge faced by aged laying hens during this phase is a decline in both production performance and egg quality. This decline can be partly attributed to their relatively reduced intestinal function ( Gan, et al, 2020 ; Abdollahi et al, 2021 ; Feng, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Morphometric traits, such as villus height (VH), crypt depth (CD), villus height to crypt depth ratio (VH/CD), and villus surface area (SA), were determined at a magnification of 40X using a light microscope. The mean value of 10 villi per sample was used for further analysis [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dietary ber, derived from cell wall of plants, consists of three major forms including soluble oligosaccharides, insoluble non-viscous ber and soluble high molecular weight polysaccharides (Abdollahi et al 2021). These types of ber vary in their nutritional properties depending on molecular weight, sugar composition and interaction with other compounds (Koca et al 2015).…”
Section: Introductionmentioning
confidence: 99%